IMPLEMENTASI LEAN CONSTRUCTION UNTUK MENINGKATKAN EFISIENSI PROYEK - Edison Hatoguan Manurung; Kerlima Hutagaol; Dizzy Putrafakhmi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The construction industry in Indonesia still faces various classic problems such as time delays, cost overruns, low labor productivity, and high levels of waste in project implementation. One construction management approach developed to address these issues is Lean Construction. This concept focuses on eliminating waste, increasing value for project owners, and continuously optimizing workflows. This study aims to examine the implementation of Lean Construction in improving construction project efficiency. The research method used was a literature review and conceptual analysis of Lean Construction principles, methods, and tools commonly applied to construction projects. The study results indicate that the application of Lean Construction through waste identification, the Last Planner System, continuous improvement, and collaboration between project parties can improve time efficiency, cost efficiency, and work quality. Therefore, Lean Construction can be used as a strategic approach in construction project management, oriented towards improving overall project performance.